2002
DOI: 10.1210/jc.2002-020493
|View full text |Cite
|
Sign up to set email alerts
|

Increased Central Arterial Stiffness in Hypothyroidism

Abstract: Hypothyroidism is associated with cardiovascular dysfunction. It is increasingly apparent that stiffening of central arteries may lead to increased afterload and cardiac dysfunction. We noninvasively studied the peripheral and central pressure waveforms in 12 untreated hypothyroid patients as well as in 12 age-, sex-, and body mass index-matched controls using the technique of pulse wave analysis from recordings at the radial artery. Indexes of arterial stiffness, augmentation index (AI) and augmentation of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 26 publications
2
82
1
6
Order By: Relevance
“…It is increasingly apparent that stiffening of central arteries may lead to increased afterload and cardiac dysfunction. 3 When arterial stiffness parameters were assessed with respect to their relationships with other studied parameters in patients, central aortic pressure showed significant relationships with serum vitamin B12 and phosphorus levels, whereas augmentation indexes had significant correlations, albumin, and magnesium levels. 4 Impaired renal function may be associated with increased arterial stiffness.…”
Section: To the Editormentioning
confidence: 93%
“…It is increasingly apparent that stiffening of central arteries may lead to increased afterload and cardiac dysfunction. 3 When arterial stiffness parameters were assessed with respect to their relationships with other studied parameters in patients, central aortic pressure showed significant relationships with serum vitamin B12 and phosphorus levels, whereas augmentation indexes had significant correlations, albumin, and magnesium levels. 4 Impaired renal function may be associated with increased arterial stiffness.…”
Section: To the Editormentioning
confidence: 93%
“…Hypothyroidism also affects systolic blood pressure levels. It is suggested that development of systolic and diastolic high blood pressure in hypothyroid patients was due to an increase in peripheral vascular resistance 31) and arterial stiffness 32) , respectively. Arterial stiffening can be evaluated by brachial-ankle pulse wave velocity.…”
Section: Lipid Profilementioning
confidence: 99%
“…Hypothyroidism: there is evidence to suggest that in patients with hypothyroidism the arterial stiffness (including that of the thoracic aorta) is increased (60,61). Clinical data are limited to a few case reports on patients with thoracic aortic disease and hypothyroidism (62,63).…”
Section: Other Potential Clinical Markers Of Thoracic Aortic Diseasementioning
confidence: 99%